Physical parameters of the cachimbal river sub-basin associated to landscape change in Pinheiral-RJ, Brazil (Bioscience Journal, 2018)
The objective of this study was to characterize the physical parameters of the Cachimbal River Watershed, located in Pinheiral, Rio de Janeiro State, Brazil, and to use the resulting data to identify degradation risks. To achieve this purpose, a Hydrologically Consistent Digital Elevation Model (HCDEM) was generated using contour line, river path, and area boundary data extracted from topographic maps of the cities of Volta Redonda (Page SF-23-ZAV-2) and Piraí (Page SF-23-Z-VI-1). These maps were obtained from the Brazilian Institute of Geography and Statistics, and were rendered at a scale of 1:50,000 ArcGISs version 10.5 software was used to generate the HCDEM, from which the physical parameters were extracted. Results showed that the altitude of the area ranges from 360 m to 740 m, while the slope varies heterogeneously from 6% to 28%. The sub-basin has a total area of 104.15  km², a perimeter of 63.41 km, a main channel length of 21.79 km, and a 5th-order dendritic drainage network. Other parameters include a compactness coefficient of 1.74, a form factor of 0.34, and a circularity ratio of 0.33. These values indicate that the sub-basin is not prone to floods because of its elongated shape. Meanwhile, drainage density was 2.60 km km-2, while river density was 5.5 channels km-2; these parameters indicate excellent performance and high potential to generate new channels. Although the roughness coefficient indicates that the area is suitable for agricultural development, the roughness index demonstrates the need to adopt more nuanced agricultural practices that account for the particular features of the area, such as topographic variation and soil characteristics.